PENGGUNAAN DIKSI DALAM NOVEL “PERGI” KARYA TERE LIYE - Syafi’ Junadi; Mariana Mariana (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
Diction is a diction or a choice of words which includes an understanding of which words are used to convey an idea, how to form the right grouping of words or use appropriate expressions, and which style is best used in a situation. The GorysKeraf divides meaning into two types, namely denotation meaning and connotation meaning. Then divide the change of meaning into six types, namely expansion of meaning, narrowing of meaning, amelioration, observation, metaphor and metonymy. There are two formulation of the problem in this study, namely (1) How is the variation of the use of diction in the novel "Go" by TereLiye, (2) How does the meaning of diction change in the novel "Go" by TereLiye. The purpose of this study is (1) to describe variations in diction on the novel "Go" by TereLiye, (2) describe how changes in the meaning of diction in the novel "Go" by TereLiye.The research method used in this research is descriptive qualitative research method. The object of this research is the variation of diction and changes in the meaning of diction according to GorysKeraf. The source of data used in this study is the novel "Go" by TereLiye. Data collection techniques in this study are determining the novel to be studied, reading repeatedly, giving a code or mark on the sentence to be studied, identifying and sorting data accompanied by discussion. Based on the analysis concluded that the novel "Going" by TereLiye tells about telling many things about life including telling the importance of loyalty and how to deal with a cool head when someone has betrayed, a friend who has various characters that sometimes irritate, and also facing family life that will not always live in harmony.